2021
DOI: 10.1016/j.conctc.2021.100762
|View full text |Cite
|
Sign up to set email alerts
|

Strength and awareness in action: Feasibility of a yoga-based intervention for post-acute mild TBI headaches among veterans

Abstract: Background Mild traumatic brain injury (mTBI) is a signature injury sustained by Veterans during recent conflicts. For some, mTBI/concussion is associated with disabling symptoms, including post-concussive headaches (PCH). However, there are limited evidence-based treatments for persistent PCH. Objective Investigators assessed the feasibility of design elements of a yoga-based interventional trial for PCH among Veterans, as well as the acceptability of the intervention.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Motion-sensor apps have been incorporated into smart phones and it is possible that the ability to unobtrusively capture some participant activities, like walking, balance, and physical activity participation will grow over time [55]. Conducting follow-up studies of injured individuals post-discharge is not without challenges, such as participant retention [19] and compliance with data collection protocols [56]. EMA studies have generally shown good retention [35,42] and participant compliance with data collection prompts [52].…”
Section: Discussionmentioning
confidence: 99%
“…Motion-sensor apps have been incorporated into smart phones and it is possible that the ability to unobtrusively capture some participant activities, like walking, balance, and physical activity participation will grow over time [55]. Conducting follow-up studies of injured individuals post-discharge is not without challenges, such as participant retention [19] and compliance with data collection protocols [56]. EMA studies have generally shown good retention [35,42] and participant compliance with data collection prompts [52].…”
Section: Discussionmentioning
confidence: 99%
“…Further, preliminary evidence suggests that participating in LoveYourBrain yoga leads to improvements across other outcomes, including QoL, among people with TBI of all severities [ 28 - 30 ]. Preliminary evidence suggests that yoga-based programs may be feasible and acceptable for individuals with mTBI+chronic pain [ 31 ]. However, the impact of yoga in general, as well as the impacts of LoveYourBrain yoga, on pain outcomes in the mTBI+chronic pain population is yet to be tested.…”
Section: Introductionmentioning
confidence: 99%